Urgensi Perlindungan Investasi Terhadap Risiko Ketidakpastian Perizinan Yang Dihadapi Investor Asing Dalam Praktik Penanaman Modal Di Indonesia - Alim, Muhammad Zahid (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Indonesia's investment legal system has established the principle of equal treatment between foreign and domestic investors, as stipulated in Law Number 25 of 2007 concerning Investment. A fast and transparent licensing system will reduce administrative costs and accelerate project implementation. These efforts will increase investor confidence, improve Indonesia's image as an investment-friendly country, and encourage more inclusive economic growth. Normative legal research, or legal research, utilizes both normative and conceptual juridical approaches. Three research approaches are used: a statutory (statistical) approach, a conceptual (conceptual) approach, and a comparative approach. The research results show that Indonesia's investment licensing system has a significant influence on foreign investment interest and realization. Indonesia's licensing policy strategy needs to be directed at accelerating the licensing process and strengthening business certainty by adopting best practices from Vietnam and Thailand